African Economic Performance in 2004 A Promise of Things to Come? - Pinaud, Nicolas (OECD Development Centre Policy Insights, 2005)
Against a backdrop of sustained global growth and high commodity prices, Africa has experienced its best economic performance in many years. While recent economic performance is not merely driven by favourable external factors, African economies still lack proper "shock-absorbers" to withstand internal (e.g. drought and floods, political instability, HIV-Aids, etc.) and external (e.g. volatility of commodity prices and exchange rates) shocks alike. They remain strongly vulnerable. In this context, creating the conditions for the development of indigenous drivers of economic activity (starting with a thriving local private sector) is a top priority